REGULATION URGENCY CONCERNING ADMINISTRATIVE SANCTION GUIDELINES IN SPACE ADMINISTRATION - Rakhmat Bowo Suharto (Jurnal Pembaharuan Hukum, 2019)
The spatial development can be supported by sustainable development, efforts are needed to divert space through the imposition of sanctions on administration in the spatial field. In the context of a legal state, sanctions must be taken while ensuring their legality in order to provide legal protection for citizens. The problem is, the construction of administrative regulations in Law No. 26 of 2007 and PP No. 15 of 2010 contains several weaknesses so that it is not enough to provide clear arrangements for administrative officials who impose sanctions. For this reason, an administration is required which requires administrative officials to request administrative approval in the spatial planning sector. The success of the regulation requires that it is the foundation of the welfare state principle which demands the government to activate people's welfare. 15 of 2010, the main things that need to be regulated therein should include (1) the mechanism of imposing sanctions: (2) determination of the type and burden of sanctions; and (3) legal protection and supervision by the region.